A LabVIEW-Based Virtual Instrument System for Laser-Induced Fluorescence Spectroscopy. (15th October 2011) - Wu, Qijun; Wang, Lufei; Zu, Lily
Abstract : We report the design and operation of a Virtual Instrument (VI) system based on LabVIEW 2009 for laser-induced fluorescence experiments. This system achieves synchronous control of equipment and acquisition of real-time fluorescence data communicating with a single computer via GPIB, USB, RS232, and parallel ports. The reported VI system can also accomplish data display, saving, and analysis, and printing the results. The VI system performs sequences of operations automatically, and this system has been successfully applied to obtain the excitation and dispersion spectra of α -methylnaphthalene. The reported VI system opens up new possibilities for researchers and increases the efficiency and precision of experiments. The design and operation of the VI system are described in detail in this paper, and the advantages that this system can provide are highlighted.